Definition of the linearity loss of the surface temperature in static tensile tests - A. Risitano; G. Fargione; E. Guglielmino (Fracture and Structural Integrity)
Static traction tests on material samples for mechanical constructions have pointed out the loss of linearity of the specimen surface temperature with the applied load. This phenomenon is due to the heat generation caused by the local microplasticizations which carry the material to deviate from its behavior, perfectly thermoelastic. The identification of the static load which determines the loss of linearity under the temperature stress becomes extremely important to define an initial dynamic characterization of the material. The temperature variations that can be read during the static loads applications are often very limited (a few tenths of degree for every 100 MPa in steels) and they require the use of special temperature sensors able to measure the temperature variations. The experience acquired in such analysis highlighted that, dealing with highly accurate sensors or with particular materials, the identification of the first loss of linearity can be influenced by the investigator himself mainly for the above mentioned limited temperature variations which can lead to incorrect estimations, sometimes really significant. Checking the validity and the above mentioned observations on the different steels, this work proposes the application of the autocorrelation function to the data collected during the application of a static load in order to make the results of the thermal analysis free from the sensitivity of the operator and also to make the result as objective as possible in order to detect the time of the loss of linearity of the temperature-time function.